Hideous Progenies : Dramatizations of "Frankenstein" from the Nineteenth Century to the Present - Forry, Steven Earl (University of Pennsylvania Press, 2016)
In Hideous Progenies, Steven Earl Forry offers a historical overview of the legend of Frankenstein's transformation over time--beginning with Shelley's original and the earliest popular dramatizations of it and continuing on through the advent of cinema.